تحديد العوامل المؤثرة على بدلات الإيجار للوحدات السكنية في مدينة اللاذقية دراسة ميدانية - العساف بيير (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aims to specify factors affecting the rental value of furnished residential units in Latakia، Syrian Arab Republic and analyzing the impact of these factors on the rent value. The study period was chosen during the current Syrian crisis. An exploratory study was conducted to determine these factors according to the local market، followed by a descriptive study that analyzes the relationship between the rent value in different areas of the city and the variables related to the affecting factors. The analysis was performed using multiple linear regression analysis. We found that the variables (factors) affecting the value of rents of furnished residential units explain 84% of the change in the independent variable which is the rent of the housing unit. The study found that: The Floor area، building age، quality of furniture، quality of finishing، number of open directions of residential unit، building services، noise، pollution، reputation of the area and distance from public services، are the factors influencing rents value of residential units in Latakia city. The study also found that the greater the area of ​​the residential unit، one meter، the higher the rent value of 344.12 SP. The lower the age of the residential unit than the other 15 years، the value of the rental value was 4681.62 SP more. The rental value of a residential unit located in a building in which services are available against one has no services is higher by 7240.73 SP، and there are other findings related to the rental change corresponding with the rest of influencing factors. تهدف هذه الدراسة إلى تحديد العوامل المؤثرة على قيمة بدلات الإيجار للوحدات السكنية المفروشة في مدينة اللاذقية، الجمهورية العربية السورية وتحليل مدى أثرها على قيمة بدل الإيجار للوحدة السكنية، حيث تمً اختيار فترة الدراسة أثناء الأزمة السورية بسبب تغير الظروف عن الفترة التي سبقت هذه الأزمة. تمّ إجراء دراسة استكشافية لتحديد هذه العوامل وفق خصوصية السوق المحلية في مدينة اللاذقية، تلاها بحث وصفي استنتاجي يحلل العلاقة بين بدلات الإيجارات في مناطق مختلفة المدينة والعوامل المؤثرة على بدل الإيجار للوحدة السكنية التي تمّ تحديدها بالدراسة الاستكشافية وهي: بعد الوحدة السكنية عن مركز المدينة، المساحة، عدد الغرف، ارتفاع الطابق، عمر البناء، جودة الإكساء، جودة الأثاث، عدد الاتجاهات المفتوحة للوحدة السكنية، خدمات البناء، الضجيج، التلوث، سمعة المنطقة، والبعد عن خدمات المدينة. تم التحليل باستخدام الانحدار الخطي المتعدد (Multiple Linear Regression Analysis) فوجدنا أن المتغيرات المحددة للعوامل المؤثرة على بدل الإيجار للوحدة السكنية قد فسرت 84% من التغير في المتغير المستقل وهو بدل إيجار الوحدة السكنية. مما توصلت الدراسة إليه أيضاً أنه كلّما زادت مساحة الوحدة السكنية متراً واحداً ارتفعت قيمة بدل الإيجار 344.12 ل.س. كلّما نقص عمر الوحدة السكنية عن غيرها 15 سنة ارتفعت قيمة بدل الإيجار 4681.62 ل.س، يزيد بدل إيجار الوحدة السكنية الموجودة في بناء تتوافر فيه خدمات عن آخر لا تتوافر في بناءه خدمات بقيمة 7240.73 ل.س، وغير ذلك من التغيرات في بدلات الإيجار بتأثير تغير العوامل المؤثرة عليها.